Recent Advances in N‐Heterocyclic Carbene Catalyzed Oxidative Cyclization for the Formation of Heterocycles. Issue 8 (9th July 2021) - Pavithra, T.; Devi, E. Sankari; Maheswari, C. Uma
Abstract: Oxidative N‐heterocyclic carbene catalyst mediated cyclization proved to be an efficient strategy for the construction of various N‐ and O‐ heterocycles. Among several metal‐free methods available for the construction of heterocyclic compounds, oxidative NHC catalysis proved to be an elegant and efficient strategy as several enantioenriched compounds with excellent enantioselectivities can be synthesized in good yields. The most common method of the generation of these heterocycles proceeds via the commonly encountered intermediate in oxidative NHC catalysis (i. e.) acyl azolium intermediate. This intermediate proves to be the active species as it can undergo reaction with suitable substrates leading to the formation of numerous N‐ and O‐ heterocycles. Herein, recent reports on different strategies that enable formal [2+2], [3+2], [3+3], [4+2] or [4+3] annulations between the incoming substrates and acyl azolium species or other active intermediates which can add to suitable substrate leading to various heterocycles were summarized. Abstract : Recent updates in the oxidative N‐heterocyclic carbene catalyzed cyclizations leading to the formation of various N‐ and O‐heterocycles were summarized in this mini‐review. Systematic classification of several heterocyles based on the formation of new rings and mechanism of important strategies were provided. Most of the reaction proceeds via acyl azolium intermediate which adds with suitable substrates to generate numerous heterocycles.